Multicultural Problem-Based Learning: Strategies for Improving Religious Moderation in Elementary Schools - Rudianto, Apip; Maftuh, Bunyamin; Agustin, Mubiar; Syaodih, Ernawulan; Anwar, Rosihon (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2025)
This study examines teachers’ perceptions of the relevance and effectiveness of Multicultural Problem-Based Learning (MPBL) in strengthening religious moderation attitudes among Elementary School and Madrasah Ibtidaiyah students in Kuningan Regency, Indonesia. A quantitative survey approach was employed using a questionnaire developed from key dimensions of religious moderation, namely national commitment, religious tolerance, appreciation of religion-based local culture, and religion-based anti-violence, as well as indicators of the importance of MPBL in primary education. The results indicate that teachers overwhelmingly perceive MPBL as a highly relevant and effective learning approach. MPBL is considered capable of strengthening students’ character in appreciating diversity, reducing negative stereotypes and prejudice, and fostering critical, collaborative, and solution-oriented thinking skills. Teachers also agree that this approach supports the internalization of tolerance, respect for different religious beliefs, and appreciation of local cultural wisdom rooted in religious values. However, the findings reveal that students’ deeper understanding of the universal principle that all religions teach peace has not been fully internalized, indicating a gap between cognitive understanding and affective–behavioral development.